Risk Management in Construction Projects in Palestine: Contractors’ Perspective - Mahamid, Ibrahim (Revista Ingeniería de Construcción, 2024)
This study is conducted to identify the main risks in construction projects in Palestine from contractors’ perspective. Questionnaire survey is the tool used to achieve the objectives of the study. 41 critical risk factors in projects associated with project duration were identified and classified as external and internal factors. The risk map for the investigated causes created based on their perceived severity and frequency of occurrence. The findings revealed 29 causes in the red zone of the risk map, 11 in the yellow zone and 1 in the green zone. The top severe risk factors are: delayed payments by the owner, closure and siege by the authorities, poor site supervision, segmentation of the Palestinian governorates, late payments to subcontractors, change orders by frequent adjustments of the owner, lack of qualified labors, unrealistic completion date of projects, weather conditions, and rework due to noncompliance with contract documents.